Silicon micromachining with nanometer-thin boron masking and membrane material. (18th October 2019) - Liu, Xingyu; Italiano, Joe; Scott, Robin; Nanver, Lis K
Abstract: Chemical-vapor-deposition (CVD) conditions were investigated for enabling the growth of pure boron (PureB) on Si with low stress and at as low as possible temperature. The application of the B as masking material for Si wet etching by tetramethyl ammonium hydroxide (TMAH) and as membrane material was demonstrated for B deposition temperatures down to 300 °C. Layer thickness in the range 4 nm to 40 nm was applied. In a Si epitaxy reactor system a close to zero-stress condition was found at ∼600 °C, and in an atomic-layer deposition system operated in CVD mode, loosely-bonded 300 °C layers without measurable stress were realized. The compactness of the layers was evaluated by monitoring the etch rate in standard aluminum wet etchant and by observing electron transmissivity, confirming a clear relationship between deposition conditions, compactness and stress.